Colonizable probiotic Lactobacillus paracasei R3 enhances ICI therapy via modulating PBMCs differentiation - Song, Wencan; Liu, Jizhen; Yang, Jingfang; Chen, Tao; Zhu, Jiayi; Liu, Xia (Frontiers in Microbiology, 2025)
Lactobacillus paracasei R3 (L.p R3) has been reported to be effective to improve anti-tumor therapy for anti-tumor treatment in immune checkpoint inhibitor (ICI) therapy for colorectal cancer. However, the mechanisms behind this remain unclear. The present study shows that L.p R3 significantly enhanced anti-tumor efficacy ICI therapies in various tumor. Our results also showed the rapid adherence of L.p R3 to intestinal epithelial cell membrane, and promoted intestinal epithelial cell expression of mucin mRNA, led to the long maintenance of L.p R3 in colon and cecum in mice. L.p R3 significantly elevated the levels of macrophages, CD4+T cells and CD8+T cells in PBMCs while simultaneously decreasing the level of programmed cell death protein 1 (PD-1) on the surface of CD4+T cells and CD8+T cells. In addition, indole-3-carboxaldehyde, a metabolite of L.p R3 serves as an aryl hydrocarbon receptor (AHR) ligand regulating immune responses, was significantly upregulated in the serum of mice orally treated with L.p R3. In summary, our findings provide novel insights into the immune regulation of probiotics in anti-tumor responses and present a potential avenue for L.p R3 in promoting ICI efficacy.